Etnophysics and Water Conservation Values in the Ruwat Ritual of Jolotundo Temple toward SDG 6 - Putri Lintang Utami (Prodi S2 Pendidikan Fisika Universitas Negeri Surabaya, 2026)
This study explores the concept of etnophysics in the context of the Ruwat ritual at the Jolotundo Temple, focusing on its relevance to Sustainable Development Goal 6 (Clean Water and Sanitation). The Ruwat ritual, a traditional Javanese purification ceremony centered around sacred water, embodies deep physical, ecological, and spiritual values. Through qualitative ethnographic methods this research identifies the implicit physics concepts underlying the ritual practices. The findings reveal that the Ruwat ritual not only represents a form of cultural heritage but also reflects indigenous knowledge systems that align with sustainable water management practices. By interpreting these local traditions through an ethnophysics lens, the study emphasizes the importance of integrating cultural wisdom into science education and environmental conservation. This integration provides a contextualized learning model that strengthens students’ understanding of physics concepts while fostering awareness of sustainability and cultural identity. The research concludes that the Ruwat ritual of Jolotundo Temple serves as a living example of how local culture can contribute to global sustainability goals, particularly in promoting responsible water use and conservation ethics.